Analisis Manajemen Pengelolaan Bisnis Budidaya Magot Perspektif Ekonomi Islam - Zainuddin, Zainuddin; Dzikrulloh, Dzikrulloh (MADINAH, 2020)
Magot is a maggot produced from black fly eggs (BSF) which is very active in breaking down organic waste and has a high protein content that can be utilized properly for animal feed etc. magot is the main attraction for business actors. It becomes very important to examine how the management of the business is managed. Therefore, the author takes the title "business management management of magot cultivation from an Islamic economic perspective". The research method used is a qualitative research method, in which the data search process is carried out through observation, interviews, and documentation techniques. This method was chosen for in-depth and comprehensive research data regarding the analysis of magot cultivation processing. This study aims to analyze the management of the magot cultivation business from an Islamic economic perspective. When the management of the magot cultivation business is managed properly, the related management can be known and can be utilized optimally. The result of this study is the management of magot cultivation from an Islamic economic perspective.